Injury incidence and specific injury patterns in app-based bodyweight training (Freeletics): results of an international survey with 3668 participants - G. Hertel; A. Hochrein; C. Suren; P. Minzlaff; I. J. Banke; J. Willers; R. von Eisenhart-Rothe; P. M. Prodinger (BMC Sports Science, Medicine and Rehabilitation, 2022)
Abstract Background The aim of this study was to analyze incidences and sport-specific injury patterns among users of a bodyweight-based training method instructed by a smartphone app (Freeletics Bodyweight App). Methods An online questionnaire based on current validated epidemiological observation methods was designed using the statistic website Surveymonkey. Subscribers of the Freeletics Bodyweight App were contacted via an online link. Injury incidence, defined as an event leading to a training pause of at least 1 day, was recorded. The type of injury was reported and classified. Furthermore, all participants were asked whether they recognized any positive or negative effects on their subjective health status. The collected data were analyzed using Surveymonkey statistic services. Results A total of 4365 Freeletics users responded to the questionnaire, 3668 completed forms were subject of further investigation. The injury period prevalence reported by users of the Freeletics App was 24% in men and 21% in women. The most frequently reported site of injury was the shoulder (29%) and the knee joint (28%), with strains (28.5%) and other muscle injuries (14.4%) being the most frequently reported types of injuries. An injury incidence rate of 4.57 per 1000 h was calculated, with injuries occurring less frequently in experienced users. Most participants reported a distinct positive effect of the app-based training on their health status. Conclusion In comparison to other sports activities app-based bodyweight training is associated with a comparably low injury period prevalence. The vast majority of injuries were reported to have resolved within one week.